Oxidative stress after three different intensities of running - Schneider, C. D.; Barp, J.; Ribeiro, J. L.; Bello-Klein, A.; Oliveira, A. R. (Canadian Journal of Applied Physiology, 2005)
In 8 trained subjects (T) and 9 untrained subjects (UT), lipid peroxidation (LPO), total antioxidant capacity (TRAP), superoxide dismutase, catalase, and glutathione peroxidase (GPx) activities were measured in the blood before and after three different intensities of exercise on the treadmill, determined from ventilatory threshold and maximal oxygen uptake data, obtained from a maximal aerobic power test. In plasma, LPO decreased from 3589 ± 193 to 3274 ± 223 cps·mg Hb-1 (p < 0.05), and TRAP increased from 304 ± 45 to 384 ± 57 mmol·L-1 trolox (p < 0.05) after high intensity exercise in T. GPx activity increased in the T group as compared to the UT group, after exercise in moderate (25.90 ± 3.79 to 15.05 ± 3.23 nM·min-1·mg protein-1) and high (21.75 ± 4.91 to 12.1 ± 2.46 nM·min-1·mg protein-1) intensities (p < 0.05). Superoxide dismutase activity increased after exercise at low (8.35 ± 0.85 to 9.23 ± 1.03 U SOD·mg protein-1) and moderate (8.89 ± 0.98 to 10.44 ± 0.86 U SOD·mg protein-1) intensity in UT (p < 0.05). There were no changes in catalase activity. These findings indicate that exercise in this model did not increase lipid peroxidation, probably because of the alterations in TRAP and enzymatic antioxidants.